THE OUTCOMES OF MICROSCOPE ASSISTED TONSILLECTOMY WITH BIPOLAR FORCEPS, MICROSCOPE ASSISTED TONSILLECTOMY WITH THE COBLATION METHOD AND TONSILLECTOMY WITH COLD STEEL INSTRUMENTS USING A HEADLIGHT: A COMPARATIVE RETROSPECTIVE STUDY - Abhishek Srivastava; Disha Koul (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: To evaluate the outcome of microscope-assisted tonsillectomy via bipolar cautery, microscope-assisted tonsillectomy via coblation and routine cold steel tonsillectomy via the headlight. The primary objective was to ascertain the intraoperative benefit of using magnification with greater illumination. The secondary objectives were to identify the advantages of different techniques in terms of postoperative pain,hemorrhage, both primary and secondary, incidence of readmissions as well as the generation of biomedical waste. Methods: The records of all patients who underwent tonsillectomy at our hospital between 2021 and 2024 were reviewed. We classified the patients into two groups according to the surgical technique used. The patients in the three groups fulfilled the same inclusion and exclusion criteria. The protocols for pre- and postoperative treatment were identical. All the surgeries performed in this study were performed by the same surgeon. The tonsils were removed by extracapsular dissection method. Results: The patients under the microscope with bipolar cautery and coblation-assisted tonsillectomy had better visualization of the tonsillar bed, which translated to better hemostasis, a shorter operative time, minimal injury to pharyngeal muscles and no residual lymphoid tissue in the corners of the tonsillar fossa, especially the tonsillolingual sulcus and upper pole. 95% percent of the patients under the microscope with bipolar cautery assisted tonsillectomy, 94% with coblation assisted tonsillectomy, whereas 91% with head light and cold steel assisted tonsillectomy were pain free after 12 weeks (p < 0.01). The average blood loss during microscope-assisted bipolar tonsillectomy and coblation tonsillectomy was 0.5 ml, whereas that during headlight and cold steel tonsillectomy was 15ml (p < 0.01). The average surgical time was 14 min under a microscope with bipolar assisted tonsillectomy and 12 min under a microscope with coblation assisted tonsillectomy, whereas in the other groups, it was 35 min (p < 0.01). Conclusion: Bipolar cautery and coblation dissection under microscopic visualization is better than cold steel dissection with headlight in terms of intraoperative visualization, time and hemostasis. However,the pain score was same across all the groups. The amount of biomedical waste generated via the coblation technique and cold steel technique was greater.